PENINGKATAN PENGETAHUAN KADER MELALUI BUKU SAKU SEBAGAI STRATEGI KEBERHASILAN MENYUSUI PADA IBU NIFAS - Hardiningsih; Emma Anastya Puriastuti; Dyah Krisnawati Satia Pratiwi (Rena Cipta Mandiri, 2025)
Successful breastfeeding among postpartum mothers plays a key role in reducing health risks for both infants and mothers. Community health workers have a vital role educating postpartum mothers, particularly regarding successful breastfeeding. Limited resources often hinder these health workers' ability to acquire up-to-date knowledge. Pocketbooks are considered an effective and easily accessible communication tool, helping to overcome communication barriers and provide information. This study aims to evaluate the effectiveness of pocketbooks as a supportive educational tool for community health workers in improving their knowledge about successful breastfeeding among postpartum mothers. The research design is a comparative test. The study population includes all community health workers in the working area of the Sangkrah Health Center. The sampling technique used is quota sampling. This study provided an intervention in distributing pocketbooks to community health workers, who were previously given an explanation of the content of the pocketbooks and underwent a pre-test. After 14 days, the community health workers took a post-test. Data analysis was conducted using a one-group pre-test and post-test design. The results showed an increase in knowledge scores before and after the training. There was an impact of distributing pocketbooks on the knowledge of community health workers about successful breastfeeding.